The Influence of Budgeting on Operational Efficiency in Seulawah Kupi - Harahap, Lokot Muda; Fauzan, Itsqon Wafi; Siagian, Hanna Maria; Karnance, Sri Ningsi; Girsang, William (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
This study aims to determine and examine the effect of budgeting variables on operational efficiency in Seulawah Kupi. This research uses quantitative research methods. Data collection in this study was obtained through distributing questionnaires to employees and buyers at Seulawah Kupi. The sample in this study amounted to 100 respondents. The sampling technique used is non probability sampling. The data analysis used in this study used simple linear regression. The results of this study concluded that budgeting has no significant effect on operational efficiency, in the simple linear regression test results with a significance value of 0,924> 0,05. In the classic assumption test, the normality test found 0,056> 0,05 which means the data is normally distributed. Then in the homogeneity test, the sig value is 0,213> 0,05, which means that the data is homogeneous, and in the multicollinearity test, a tolerance value of 1,000> 0,100 and VIF 1,000 < 10,00 is found, which means that the effect of budgeting on operational efficiency in Seulawah Kupi does not occur Multicollinearity.